Shaping the new world of work: the impact of digitalisation and robotisation. Conference report. ETUI-ETUC Conference, Brussels, 27-29 June 2016 - Watson, Rory; Stafford, Owen (Brussels, 2016)
"This report summarises the presentations and debates of the 3-day ETUC/ETUI conference on 'Shaping the new world of work. The impacts of digitalisation and robotisation', held from 27-29 June 2016 in Brussels."